INTERACTION OF MATHEMATICAL ABILITIES AND THE CHOICE OF A VOCATIONAL CAREER - Tomėnienė, Laima; Baranauskienė, Ingrida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article analyzes vocational education teachers‘ approach to the interaction between mathematical competence and working-class career choice in the educational process of the students with mathematics learning difficulties. There are distinguished basic mathematical subjects and mathematical skills, which, according to the teachers, are important and necessary for successful vocational training (learning).